2021
DOI: 10.1007/s40201-020-00604-7
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of cooking appliances and residential traffic proximity to aerosol personal exposure

Abstract: Purpose Indoor and outdoor factors affect personal exposure to air pollutants. Type of cooking appliance (i.e. gas, electricity), and residential location related to traffic are such factors. This research aims to investigate the effect of cooking with gas and electric appliances, as an indoor source of aerosols, and residential traffic as outdoor sources, on personal exposures to particulate matter with an aerodynamic diameter lower than 2.5 μm (PM2.5), black carbon (BC), and ultrafine particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Supplementary I nformation 2 details the main characteristics of included studies. There were 22 studies conducted in Europe; five in the UK (Wigzell et al 2000 ; Nasir and Colbeck 2013 ; O’Leary et al 2018 ; Chakraborty et al 2020 ; Shehab et al 2021 ); three in Portugal (Alves et al 2020 ; Madureira et al 2020 ; Marques and Pitarma 2020 ); two each in Sweden (Molnar et al 2005 ; Omelekhina et al 2022 ), Italy (Frasca et al 2018 ; Pietrogrande et al 2021 ) and Greece (Sarigiannis et al 2014 ; Assimakopoulos et al 2018 ); one each in Finland (Siponen et al 2019 ), Norway (Wyss et al 2016 ), Denmark (Karottki et al 2014 ), Germany (Salthammer et al 2014 ), Poland (Jedrychowski et al 2006 ), Switzerland (Monn et al 1997 ) and Belgium (Stranger et al 2009 ); and one study was multicentric (UK and the Republic of Ireland) (Semple et al 2012 ). There was only one study each from Asia (Japan) (Ohura et al 2005 ), the Middle East (Kuwait) (Yassin et al 2012 ), Oceania (Australia) (Mazaheri et al 2018 ) and South America (Chile) (Rojas-Bracho et al 2002 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary I nformation 2 details the main characteristics of included studies. There were 22 studies conducted in Europe; five in the UK (Wigzell et al 2000 ; Nasir and Colbeck 2013 ; O’Leary et al 2018 ; Chakraborty et al 2020 ; Shehab et al 2021 ); three in Portugal (Alves et al 2020 ; Madureira et al 2020 ; Marques and Pitarma 2020 ); two each in Sweden (Molnar et al 2005 ; Omelekhina et al 2022 ), Italy (Frasca et al 2018 ; Pietrogrande et al 2021 ) and Greece (Sarigiannis et al 2014 ; Assimakopoulos et al 2018 ); one each in Finland (Siponen et al 2019 ), Norway (Wyss et al 2016 ), Denmark (Karottki et al 2014 ), Germany (Salthammer et al 2014 ), Poland (Jedrychowski et al 2006 ), Switzerland (Monn et al 1997 ) and Belgium (Stranger et al 2009 ); and one study was multicentric (UK and the Republic of Ireland) (Semple et al 2012 ). There was only one study each from Asia (Japan) (Ohura et al 2005 ), the Middle East (Kuwait) (Yassin et al 2012 ), Oceania (Australia) (Mazaheri et al 2018 ) and South America (Chile) (Rojas-Bracho et al 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported its PM 2.5 concentration as an hourly mean (Wyss et al 2016 ), and another two studies as 48-h means (Wigzell et al 2000 ; Jedrychowski et al 2006 ). The remaining six studies (Olson and Burke 2006 ; Baxter et al 2007 ; O’Leary et al 2018 ; Mazaheri et al 2018 ; Alves et al 2020 ; Shehab et al 2021 ) (Table 2 ) reported their cooking related PM 2.5 concentrations over various sampling durations, thus making them difficult to group and directly compare.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to be able to hold the most polluted environments to the same standards as indoor environments with exemplary factors of indoor environmental quality, which are more easily compared when using the same metrics. Field studies characterizing the contribution of daily activities to indoor air pollution often measure and model UFP + FP concentrations in order to encompass source and loss processes of smaller aerosols generated from events such as cleaning, cooking, electric appliance usage, and outdoor air intake 27,29,109–111 . Thus, field campaigns such as this which investigate the effects of architectural design and stove variations in mitigating indoor woodsmoke aerosol concentrations must carefully consider metrics of success.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies characterizing the contribution of daily activities to indoor air pollution often measure and model UFP + FP concentrations in order to encompass source and loss processes of smaller aerosols generated from events such as cleaning, cooking, electric appliance usage, and outdoor air intake. 27,29,[109][110][111] Thus, field campaigns such as this which investigate the effects of architectural design and stove variations in mitigating indoor woodsmoke aerosol concentrations must carefully consider metrics of success. Though the common ways of deciding original and improved stove tiers based on mass metrics, such as PM 1 , PM 2.5 , elemental carbon, and brown carbon, are highly systematic and widely effective for comparing cooking environments with the same stove types, 25 it is clear that cookstoves with improved combustion such as rocket, gasifier, and air injection have the potential to release a greater abundance of particles smaller than 30 nm relative to TSFs (exemplified in distributions can be coupled with deposition fractions for the human respiratory tract to estimate inhaled deposited dose rates.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…A preliminary analysis of 72 candidates has shown that cooking was the activity where people are exposed to the highest PM 2.5 concentrations (28 µgm −3 ), followed by indoor sport (23 µgm −3 ) and outdoor leisure activities (excluding sport) (17 µgm −3 ). As shown by Shehab et al (2021) and Hu et al (2012) even cooking with an electric stove emits particulate matter, as a result of the burning of the food itself. At the bottom of the list is shopping in the city (7 µgm −3 ).…”
Section: Personal Exposurementioning
confidence: 99%